A novel local impedance algorithm to guide effective pulmonary vein isolation in AF patients: 1-year outcome from the CHARISMA Study. (25th November 2020) - Segreti, L; De Simone, A; Schillaci, V; Zucchelli, G; Pandozi, C; Pecora, D; Pelargonio, G; Arestia, A; De Lucia, R; Shopova, G; Viani, S; Ferrari, C; et al.
Abstract: Background: Recently, a novel technology able to measure local tissue impedance (LI) providing a measure of tissue characteristics aimed at validating confidently ablation endpoints has become available for clinical use. Purpose: We report the outcomes of our acute and long-term clinical evaluation of this algorithm in consecutive atrial fibrillation ablation cases. Methods: Consecutive patients (pts) undergoing AF ablation at 6 Italian centers were included in the CHARISMA registry. A novel RF ablation catheter and a dedicated algorithm were used to measure LI through the distal catheter's electrode. The ablation was guided by looking at the magnitude and time course of impedance drop during RF delivery. The maximum distance between each ablation spot (center-to-center) was suggested to be ≤4 mm. RF applications were targeted to a LI drop of 10 Ω and RF applications were stopped when a maximum cutoff LI drop of <40 Ω was observed. Successful single RF ablation was defined according with a reduction of signal voltage (RedV) by at least 50% and inability to capture local tissue on pacing. Ablation endpoint was PVI as assessed by entrance and exit block. Post-ablation, all pts were monitored with ambulatory event monitoring, as well as Holter monitoring at 3, 6, and 12 months post-ablation. Additional ECG monitoring was performed as indicated by patient symptoms. Results: A total of 1914 point by point first pass RF applications >10 s performed around PVs were analyzed from 98 pts (mean age = 61±11 years, 69% male, 55% paroxysmal AF, 45% persistent AF, 60% de novo procedures, 40% redo procedures). The mean LI was 105±15Ω prior to ablation and 92±13Ω after ablation (p<0.0001, mean absolute LI drop of 12.7±8Ω) during a median RF delivery time of 22 [17–31] sec. Effective ablation spots (88%) showed a higher absolute impedance drop (13.6±8Ω at effective RedV vs 6±3Ω at ineffective RedV, p<0.0001) compared with ineffective sites (12%). No steam pops or complications, including atrio-esophageal fistula or tamponade were reported during or after the procedures. At the end of the procedures all PVs were successfully isolated in all study pts. During a median follow-up of 369 [287–446] days, 13 pts (13.2%) developed an AF/AT recurrence after the 90-days blanking period (9.2% with paroxysmal vs 18% with persistent AF, p=0.239; 8.5% for de novo vs 20.5% for redo procedures, p=0.127). The time to recurrence was comparable among AF type (HR=1.97; 0.66 to 5.86; log-rank p=0.2265 for persistent vs paroxysmal AF) and procedural type (HR=2.56; 0.84 to 7.82; log-rank p=0.087 for redo vs de novo procedure) Conclusions: In our experience, the magnitude of the LI drop during RF delivery was associated with effective lesion formation. An ablation strategy for PVI guided by LI technology was safe and effective, and resulted in a very low recurrence rate of AF at 1-year follow-up irrespective of paroxysmal/persistent AF type or de novo/redo procedure. Funding Acknowledgement: Type of funding source: None